2008
DOI: 10.1158/0008-5472.can-07-6655
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Methylation Mediated Silencing of MicroRNA-1 Gene and Its Role in Hepatocellular Carcinogenesis

Abstract: MicroRNAs (miR) are a class of small (f21 nucleotide) noncoding RNAs that, in general, negatively regulate gene expression. Some miRs harboring CGIs undergo methylationmediated silencing, a characteristic of many tumor suppressor genes. To identify such miRs in liver cancer, the miRNA expression profile was analyzed in hepatocellular carcinoma (HCC) cell lines treated with 5-azacytidine (DNA hypomethylating agent) and/or trichostatin A (histone deacetylase inhibitor). The results showed that these epigenetic d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
343
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(371 citation statements)
references
References 50 publications
26
343
0
2
Order By: Relevance
“…A recent analysis of the methylation signature in PCa cell lines demonstrated that indeed histone methylation leads to the silencing of the entire mir-22l/222 cluster (Ke et al, 2009). Deregulation of several of the downregulated miRNAs identified in our prognostic profile has been demonstrated also in other human malignancies or diseases such as breast ) and colorectal cancer (Michael et al, 2003) for the mir-143/145 cluster; breast cancer (Zhao et al, 2008) and glioblastoma (Gillies and Lorimer, 2007) for the mir-221/222 cluster; and liver cancer (Datta et al, 2008) or cardiac hypertrophy (Care et al, 2007) for the mir-1/ 133 cluster.…”
Section: Discussionsupporting
confidence: 60%
“…A recent analysis of the methylation signature in PCa cell lines demonstrated that indeed histone methylation leads to the silencing of the entire mir-22l/222 cluster (Ke et al, 2009). Deregulation of several of the downregulated miRNAs identified in our prognostic profile has been demonstrated also in other human malignancies or diseases such as breast ) and colorectal cancer (Michael et al, 2003) for the mir-143/145 cluster; breast cancer (Zhao et al, 2008) and glioblastoma (Gillies and Lorimer, 2007) for the mir-221/222 cluster; and liver cancer (Datta et al, 2008) or cardiac hypertrophy (Care et al, 2007) for the mir-1/ 133 cluster.…”
Section: Discussionsupporting
confidence: 60%
“…Among the various mechanisms of carcinogenesis the hypermethylation of related genes results in a reduction of the miR-1 levels. It results in the overexpression of certain oncogenes, FoxP1 and MET, as potential targets, thus promoting cell proliferation (Datta et al, 2008). Two other mechanisms of miR-1 action are given by (Wei et al, 2012;Li et al, 2012a).…”
Section: Mir-1mentioning
confidence: 99%
“…Aberrant patterns of epigenetic modifications, such as DNA methylation or histone acetylation, are important molecular mechanisms underpinning development of cancer, including HCC [72][73][74][75]. Recent evidence has suggested links between miRNAs and epigenetic pathways in hepatocarcinogenesis.…”
Section: Mirnas Add Complexity To Epigenetic Modificationmentioning
confidence: 99%